O educador de jovens e adultos e sua formação na Faculdade de Educação da Universidade Federal de Minas Gerais - Rafaela Carla e Silva Soares (2017)
The discussions that motivated this research crossed the question of the initial formation of the Educator of Youth and Adult Education. We start from the assumption that the specific formation for the YAE appears as a differential both in the performance of this educator, and in the struggle for the right of the excluded to education. We work with the hypothesis that the political scenario of Youth and Adult Education can influence the formation processes and, consequently, the action of the YAE educators. We sought to understand and analyze the formation of the educator of the Pedagogy course of the Faculty of Education of the Federal University of Minas Gerais, from the perspective of the students who chose the Complementary Formation in YAE. The research had as objective to know the profile of the educator of EJA from the FaE/UFMG, the motivations that led them to choose the emphasis in YAE, the meanings they attribute to that experience, as well as the relation of their professional insertion with the formation Initial. We did a survey of students graduated between 2003 and 2013, applied questionnaires, conducted interviews and organized a meeting / seminar. We spoke with theorists of the field of education and teacher education in general: António Nóvoa, Maurice Tardif, Paulo Freire, Bernadete Gatti, Júlio Diniz-Pereira; And with teachers training researchers for the YAE: Miguel Arroyo, Osmar Fávero, Maria Amélia Giovanetti, Maria Clara Di Pierro, Leôncio Soares, Maria Hermínia Laffin, Fernanda Silva, Rosa Porcaro. We found different reasons for the choice of Complementary Formation in Youth and Adult Education such as: previous experience with the subjects of the YAE, the interest in the subject of the studies of the area and the influence of third parties. One of the greatest contributions of the Complementary Formation in YAE to which the students mention is about getting to know both the field and the subjects of Youth and Adult Education and how it contributes to their professional performance, even if it is not with young and adult learners. We also perceived that this formation was configured as a differential in the moment of the professional insertion of the graduates. After analyzing the data and interviews, we highlight that the EJA fields has a place established in the Faculty of Education of UFMG.